Central giant cell granuloma of the jaws and giant cell tumor of long bones: A clinicopathological, cytometric and immunohistochemical comparative study - Manal A Al Sheddi; Hezekiah A Mosadomi; F H Al Dayel (Saudi Journal of Oral Sciences, 2014)
Aim: Central giant cell granuloma (CGCG) of the jaws and giant cell tumor (GCT) of bone share a number of similarities and dissimilarities in respect of their histopathological, cytometric and immunohistochemical features. The aim of this study was to compare CGCG of the jaws and GCT of long bones from clinicopathology, cytometry and immunohistochemistry aspects. Materials and Methods: 18 CGCG and 22 GCT of bones were compared. Clinical data were obtained on the age, gender, diagnosis, clinical course, treatment and follow up. Histopatholgical features of mononuclear cell; stroma and giant cells were assessed. Computer-assisted image analysis was used to measure the mean number of giant cells, mean number of nuclei per giant cell, fractional surface area and relative size index. Expression of cell differentiation markers (vimentin, CD68, CD34, S-100P, alpha-smooth muscle actin [αSMA]) and cell cycle related markers (PCNA, P53, Ki-67, bcl-2) were evaluated. Results: CGCG of the jaw showed an early age of presentation (55.6% <25 years) and the mandible was the more common anatomical location (77.8), whereas the femur and tibia were equally affected by GCT (36.4%). GCT showed higher mean number of giant cells, higher number of nuclei per giant cell, greater fractional surface area and relative size index. Both diseases showed similar cellular phenotype in respect of Vimentin, S100 protein, CD68 and CD34. There was increased immunoreactivity of GCT to Ki-67, P53 and αSMA. Conclusion: The findings suggested that the GCT and the CGCG may be variants of the same disease entity with age and site-specific features.